Stanisław Tarnowski jako badacz dziejów myśli politycznej - Koehler, Krzysztof (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2019)
The author tries to describe in the article the research method of Stanisław Tarnowski presented in his fundamental dissertation: Studies to the History of Polish Literature. Political writers of the 16th century. The work was published in 1886 and it contained strong references to the current research methodologies. As it turns out, Tarnowski opposes contemporary „scientism” (or, after MacIntyre, „encyclopedism”). He emphasizes his emotional approach, pointing to a strongly utilitarian understanding of reading passion. The category of „who harmed and who did not harm” Poland is at the same time an absolutely individual research perspective, which should perhaps be included in the romantic convention of historical literary research. The author points out that although this research perspective is very anachronistic today, it brings unexpected and very interesting readings of political texts from the 16th century, thanks to which Tarnowski’s fundamental work still has great cognitive potential.